Current Status of State-Level Maternal Mortality Review Legislation in the United States [26B]. (May 2017) - Adesomo, Adebayo; McDonald, Amanda; Oben, Ayamo G.; Rodriguez, Emma; Ireland, Kayla; Ramsey, Patrick S.
Abstract : INTRODUCTION: Over the past 20 years the United States' the maternal mortality rate has doubled. Significant racial disparities and discrepancies in reporting highlight the need for standardized case definition, uniform reporting, and comprehensive review of maternal mortality cases. Our objective was to assess the presence of state-specific legislation requiring maternal mortality reporting and review in the United States. METHODS: We surveyed all 50 states for existing laws, or pending legislation, requiring maternal mortality reporting by searching state government and other legislative websites for keywords and phrases "maternal mortality, maternal death, pregnancy-related death." Additionally, state health department officials were contacted directly to confirm the presence or absence of pertinent legislation. RESULTS: Twenty-four of the 50 states (48%) currently have active or pending legislation regarding maternal mortality reporting. Twenty-nine of the 50 states (58%) have committees specifically designated to review maternal mortality. In states with legislation compared to states without legislation or committees there were no statistically significant differences in maternal mortality ratio (18.4 vs. 22.2), minority birth rate/1000 births (3.0 vs. 2.7) or overall birth rate/1000 births (12.3 vs. 12.1). 53% of states with a maternal mortality ratio greater than 25/100, 000 have active or pending legislation. CONCLUSION: Less than half of states have active legislation requiring maternal mortality review. Review of maternal mortality cases in the United States needs to be standardized and universal to further elucidate the causes of the rising maternal mortality rate in the United States.